To Be or Not To Be…Toxic—Is RNA Association With TDP-43 Complexes Deleterious or Protective in Neurodegeneration? - Loganathan, Suvithanandhini; Lehmkuhl, Erik M.; Eck, Randall J.; Zarnescu, Daniela C. (Frontiers in Molecular Biosciences, 2020)
TAR DNA binding protein (TDP-43) is a nucleic acid binding protein associated with insoluble cytoplasmic aggregates in several neurodegenerative disorders, including 97% of the ALS cases. In healthy individuals, TDP-43 is primarily localized to the nucleus; it can shuttle between the nucleus and the cytoplasm, and is involved in several aspects of RNA processing including transcription, splicing, RNA stability, transport, localization, stress granule (SG) formation and translation. Upon stress, TDP-43 aggregates in the cytoplasm and associates with several types of RNA and protein assemblies, resulting in nuclear depletion of TDP-43. Under conditions of prolonged stress, cytoplasmic TDP-43 undergoes liquid-liquid phase separation (LLPS) and becomes less mobile. Evidence exists to support a scenario in which insoluble TDP-43 complexes sequester RNA and/or proteins causing disturbances in both ribostasis and proteostasis, which in turn contribute to neurodegeneration. However, the relationship between RNA binding and TDP-43 toxicity remains unclear. Recent studies provide conflicting views on the role of RNA in TDP-43 toxicity, with some finding RNA as a toxic factor whereby RNA binding contributes to TDP-43 toxicity, while others find RNA to be a protective factor that inhibits TDP-43 aggregation. Here we review and discuss these recent reports, which ultimately highlight the importance of understanding the heterogeneity of TDP-43 assemblies and collectively point to solubilizing TDP-43 as a potential therapeutic strategy.